Microbiology of organic and conventionally grown fresh produce - Daniele F. Maffei (Brazilian Journal of Microbiology)
ABSTRACT Fresh produce is a generalized term for a group of farm-produced crops, including fruits and vegetables. Organic agriculture has been on the rise and attracting the attention of the food production sector, since it uses eco-agricultural principles that are ostensibly environmentally-friendly and provides products potentially free from the residues of agrochemicals. Organic farming practices such as the use of animal manure can however increase the risk of contamination by enteric pathogenic microorganisms and may consequently pose health risks. A number of scientific studies conducted in different countries have compared the microbiological quality of produce samples from organic and conventional production and results are contradictory. While some have reported greater microbial counts in fresh produce from organic production, other studies do not. This manuscript provides a brief review of the current knowledge and summarizes data on the occurrence of pathogenic microorganisms in vegetables from organic production.